What is the effect of a decision aid in potentially vulnerable parents? Insights from the head CT choice randomized trial. (23rd November 2019) - Skains, Rachel M.; Kuppermann, Nathan; Homme, James L.; Kharbanda, Anupam B.; Tzimenatos, Leah; Louie, Jeffrey P.; Cohen, Daniel M.; Nigrovic, Lise E.; Westphal, Jessica J.; Shah, Nilay D.; Inselman, Jonathan; Ferrara, Michael J.; et al.
Abstract: Objective: To test the hypotheses that use of the Head CT Choice decision aid would be similarly effective in all parent/patient dyads but parents with high (vs low) numeracy experience a greater increase in knowledge while those with low (vs high) health literacy experience a greater increase in trust. Methods: This was a secondary analysis of a cluster randomized trial conducted at seven sites. One hundred seventy‐two clinicians caring for 971 children at intermediate risk for clinically important traumatic brain injuries were randomized to shared decision making facilitated by the DA (n = 493) or to usual care (n = 478). We assessed for subgroup effects based on patient and parent characteristics, including socioeconomic status (health literacy, numeracy and income). We tested for interactions using regression models with indicators for arm assignment and study site. Results: The decision aid did not increase knowledge more in parents with high numeracy ( P for interaction [ P int ] = 0.14) or physician trust more in parents with low health literacy ( P int  = 0.34). The decision aid decreased decisional conflict more in non‐white parents (decisional conflict scale, −8.14, 95% CI: −12.33 to −3.95; P int  = 0.05) and increased physician trust more in socioeconomically disadvantaged parents (trust in physician scale, OR: 8.59, 95% CI: 2.35‐14.83; P int  = 0.04). Conclusions: Use of the Head CT Choice decision aid resulted in less decisional conflict in non‐white parents and greater physician trust in socioeconomically disadvantaged parents. Decision aids may be particularly effective in potentially vulnerable parents.